Structural architecture and interplay of the nucleotide- and erythrocyte binding domain of the reticulocyte binding protein Py235 from Plasmodium yoelii - Grüber, Ardina (2013)
Human malaria is caused by the cyclical invasion of the host’s red blood cells (RBCs) by the invasive form of the parasite, the merozoite. The invasion of the RBC involves a range of parasite ligand receptor interactions, a process which is under intensive investigation. Two protein families are known to be important in the recognition and invasion of the human erythrocyte, the erythrocyte-binding like (EBL) proteins and the reticulocyte binding like proteins, of which the Py235 family in Plasmodium yoelii is a member. Recently the nucleotide binding domain (NBD94), that plays a role in ATP sensing, and the erythrocyte binding domain (EBD) of Py235, called EBD1–194, have been identified. Binding of ATP leads to conformational changes within Py235 from P. yoelli and results in enhanced binding of the protein to the RBC. Structural features of these domains have been obtained, providing the platform to discuss how the structural architecture creates the basis for an interplay of the sensing NBD and the EBD domain in Py235. In analogy to the receptor-mediated ligand-dimerization model of the EBL proteins PvDBP and PfEBA-175 from Plasmodium vivax and Plasmodium falciparum, respectively, we hypothesise that Py235 of P. yoelii binds via its EBD1–194 domain to the RBC receptor, thereby inducing dimerization of the Py235-receptor complex.